2006
DOI: 10.1111/j.1600-0560.2006.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunohistochemical assessment of the effect of cyclosporin in keratinocytes and dermal dendrocytes in psoriasis

Abstract: Cyclosporine was effective and safe for psoriasis in low doses, with significant decrease of PASI and dermal dendrocytes number after 8 weeks of therapy. CK10 and 14 pattern changed and, less prominently, CK16 expression. These modifications occur later than the PASI and dermal dendrocytes variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…We consider that our findings are not in conflict with previous reports because CyA can bring about an improvement only on the psoriatic lesions but not affect uninvolved skin. Lago et al (2007) have reported that CyA affects dermal dendrocytes and keratinocytes in psoriatic lesions, but that its main action is on T lymphocytes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We consider that our findings are not in conflict with previous reports because CyA can bring about an improvement only on the psoriatic lesions but not affect uninvolved skin. Lago et al (2007) have reported that CyA affects dermal dendrocytes and keratinocytes in psoriatic lesions, but that its main action is on T lymphocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Although the effects of CyA on keratinocytes are well documented, little is known about the effects on dermal fibroblasts (Priqnano et al 1996;Lago et al 2007). Recently, CyA has been reported to modify the synthesis and degradation of extracellular matrix (ECM) by osteoblasts and gingival fibroblasts (Boltchi et al 1999;Fu et al 1999;Fornoni et al 2001;Bostorm et al 2005;Bullon et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that combination therapy led to quicker improvements and more extensive efficacy than etanercept monotherapy alone. Lago et al 4 evaluated 30 patients with psoriasis treated with cyclosporine monotherapy for 8 weeks. Mean PASI before treatment was 26.32, and reduced to 3.71 after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐eight studies met the criteria for inclusion in the guidelines. Two grade A 2 studies on cyclosporine mono‐ therapy were included [237, 250], 14 grade B studies [243–245, 247, 251–260], and seven grade C studies [249, 261–266]. The resulting evidence level was 1.…”
Section: Systemic Therapymentioning
confidence: 99%